Outcomes of Multidetector Computed Tomography Pulmonary Angiography in Pregnant and Postpartum Women With Suspected Pulmonary Embolism. Issue 3 (August 2021) - Sun, Simon; Diaconescu, Marius; Zhe, Tian; Mesurolle, Benoit; Semionov, Alexandre
Purpose: Verify whether there is a difference in likelihood of developing pulmonary embolism (PE) between pregnant women, nonpregnant women of reproductive age, and postpartum (up to 6 weeks) women, by comparing their outcomes on computed tomography pulmonary angiography (CTPA) done for suspicion of PE. Materials and Methods: Retrospective cohort study of 1463 CTPA done for suspicion of PE in females of reproductive age (18-40 years), nonpregnant, pregnant (antepartum), and postpartum, from 2 tertiary-care academic hospitals between October 2006 and September 2015. Primary outcome was diagnosis of PE on imaging. Additional assessment was made of technical adequacy of the studies and method of delivery for the postpartum cohort (vaginal vs caesarean birth). Twenty-nine technically nondiagnostic studies were excluded. The effect of any potential variable on PE status was tested using univariate logistic regression. Subgroup analysis was performed after excluding patients with independent risk factors for PE. Results: The rate of CTPA positive for PE was less among pregnant patients compared to early postpartum and nonpregnant women of similar age, 2.9% vs 11.5% and 10.3%, respectively. Pregnancy was associated with statistically significant decreased odds ratio of developing a PE on CTPA, 0.23 (0.09-0.89), P value = .004. After excluding patients with additional independent risk factors for PE, there was no statistically significant odds ratio association between presence of PE on CTPA and pregnancy 0.41 (0.13-1.34), P value = .14. Conclusion: Rate of CTPA positive for PE in pregnant women was lower than in nonpregnant and early postpartum women. Pregnancy was statistically significantly less likely to be associated with positive PE on a CTPA study. The common perception that pregnancy (antepartum state) is associated with an increased risk of PE may require a thorough critical reappraisal.